2021
DOI: 10.3389/fcvm.2021.758956
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Circulating Proprotein Convertase Subtilisin/Kexin Type 9 Concentrations and Cardiovascular Events in Cardiovascular Disease: A Systemic Review and Meta-Analysis

Abstract: Background: A large amount of evidence suggests that proprotein convertase subtilisin/Kexin type 9 (PCSK9) inhibitors have clinical benefits in patients with cardiovascular disease (CVD). However, whether PCSK9 concentrations predict future cardiovascular (CV) events remains unclear.Methods: We conducted a meta-analysis to investigate the ability of PCSK9 concentrations to predict future CV events in patients with established CVD. A comprehensive search of electronic databases was conducted in June 2021. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…PCSK9, as a trigger for the expression of pro-inflammatory cytokines, is significantly elevated during ACS ( 23 , 39 ). Several studies found that it was positively associated with the risk of cardiovascular events, which may be related to multiple mechanisms, such as inflammatory cascade activation and additional platelet release and aggregation ( 40 42 ). Early PCSK9 inhibitor treatment can potentially inhibit PCSK9-related inflammatory effects in patients with ACS.…”
Section: Early Pcsk9 Inhibitors and Inflammatory Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCSK9, as a trigger for the expression of pro-inflammatory cytokines, is significantly elevated during ACS ( 23 , 39 ). Several studies found that it was positively associated with the risk of cardiovascular events, which may be related to multiple mechanisms, such as inflammatory cascade activation and additional platelet release and aggregation ( 40 42 ). Early PCSK9 inhibitor treatment can potentially inhibit PCSK9-related inflammatory effects in patients with ACS.…”
Section: Early Pcsk9 Inhibitors and Inflammatory Indicatorsmentioning
confidence: 99%
“…release and aggregation (40)(41)(42). Early PCSK9 inhibitor treatment can potentially inhibit PCSK9-related inflammatory effects in patients with ACS.…”
Section: Lipid-lowering Effect Of Pcsk9 Inhibitors and Early Implemen...mentioning
confidence: 99%
“…13 Accumulating evidence has demonstrated that elevated circulating PCSK9 level has been associated with increased CVD risk. 14 Although multiple randomised controlled trials (RCTs) and meta-analyses have demonstrated the efficacy of PCSK9 inhibitors in treating dyslipidaemia, several studies have reported that conventional lipid-lowering therapies could lead to increased circulating PCSK9 levels. [15][16][17][18][19][20] On the other hand, it has been reported that statin treatment raises PCSK9 in primarily the inactivated form.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…PCSK9 is a serine protease that binds to the LDL receptors on the cellular membrane of hepatocytes, inhibiting LDL receptor recycling and promoting its lysosomal degradation, which results in elevated plasma LDL-C as well as promotes vascular remodelling and atheroma development 13. Accumulating evidence has demonstrated that elevated circulating PCSK9 level has been associated with increased CVD risk 14. Although multiple randomised controlled trials (RCTs) and meta-analyses have demonstrated the efficacy of PCSK9 inhibitors in treating dyslipidaemia, several studies have reported that conventional lipid-lowering therapies could lead to increased circulating PCSK9 levels 15–20.…”
Section: Introductionmentioning
confidence: 99%